Integrasi Tashfiyah dan Tarbiyah sebagai Pondasi Psikoterapi Islam: Kajian Konseptual - Muhammad Cholid Abdurrohman (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Islamic psychotherapy has emerged as a response to the limitations of mainstream psychotherapeutic approaches that tend to adopt secular paradigms and insufficiently accommodate the spiritual dimension of Muslim clients. This article aims to examine and conceptualize the integration of tashfiyah (purification of the soul) and tarbiyah (continuous moral and psychosocial development) as a foundational framework for Islamic psychotherapy. The study employs a qualitative approach using a critical literature review of peer-reviewed journal articles, academic books, and systematic reviews in the fields of psychology of religion, mental health, and Islamic counseling. The findings indicate that tashfiyah functions as an intrapersonal therapeutic mechanism addressing spiritual purification, emotional regulation, and meaning reconstruction based on Islamic values, while tarbiyah serves as a preventive and rehabilitative psychosocial framework that sustains psychological change through value internalization and community support. The integration of these two principles results in a holistic and contextually grounded model of Islamic psychotherapy that extends beyond symptom reduction toward the transformation of life orientation and moral character. Nevertheless, this study also highlights the limited availability of empirical evidence supporting the clinical effectiveness of tashfiyah–tarbiyah-based psychotherapy. Further empirical research employing rigorous methodological designs is therefore required to validate the proposed model as an evidence-based practice in contemporary mental health care.